Koreografi Tari Uraklah Simpuah Di Sanggar Tak Kondai Nagari Pasir Talang Kecamatan Sungai Pagu Kabupaten Solok Selatan - Yosi Muliana; Herlinda Mansyur (SENDRATASIK UNP, 2020)
This is a descriptive qualitative research using a descriptive analysis method. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing instruments and cellphones. The data used where primary and secondary data. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted through data collection, data reduction, data presentation, and conclusion making. The results of this study show that the Uraklah Simpuah Dance is cultivated from social condition which is not in accordance with the customs in the village. The situation meant isgetting around done by Minangkabau women. In the form aspect, there is a floor design used in Uraklah Simpuah dance. It is a straight floor design which is lined and curved in a circle. It uses large group composition (unison). The music instrument used in this dance is a drum namely gandang tambua. In addition, it uses the distinctive strains of songs to accompany the dance.The costume worn is a basic black velvet shirt paired with songket and a red to orange head cover. This dance also uses metal plates and resins as the sounds. Thus, it is concluded that the Uraklah Simpuah dance is a traditional dance which already has choreographic aspects so that it can be researched using choreography.